History of Relationship Between Republic of Korea and Japan, 1965-2009 - Chartprasert, Nophadol (Thai Journal of East Asian Studies, 2018)
This research aims to study the history of the relationship between Japan and Republic of Korea from 1965 to 2009. From the study, the relationship can be divided into 3 periods: 1965–1983, 1983–2001 and 2001–2009. The relationship has gradually transformed from tensional and confrontational relations in the 1960s and the 1970s to become more interdependent since 1980s. However, since the 1980s, tensions between the two countries have occasionally occurred. Consequences of conflicts in the past, territorial disputes, security problems in the East Asia, the alignments with the US, economic developments and domestic politics can be considered as major factors which have determined the relationship between these two countries during the mentioned period.